Analisis Pengaruh Working Capital Management, Capital Structure, Total Asset Turnover Terhadap Profitabilitas Perusahaan - Grace King; Agustin Ekadjaja; Malem Ukur Tarigan (Universitas Kristen Krida Wacana, 2014)
ABSTRACTThe purpose of this research was to examine the effect of current ratio, size, debt to equity ratio, total asset turnover on profitability. The data is obtained from Information Centre of Stock Exchange Faculty of Economy Tarumanagara University. The sample chosen are the real estate company listed in BEI for 2010-2012. Data analysis method used are t-test and F-test. The test result partially showed that debt to equity ratio, total asset turnover have effect on profitability.Keywords: Current Ratio, Size, Debt To Equity Ratio, Total Asset Turnover And Profitability